"Your English is Good for an Immigrant": Examining Mixed Effects of Mindset Messages on Perceived Linguistic Potential of and Blame Attributions Towards ESL Migrants. (June 2023) - Lou, Nigel Mantou; Noels, Kimberly A.
Social exclusion can exacerbate newcomers' language difficulties and undermine their social integration. We examined whether language mindsets induce mixed attitudes towards migrants with limited proficiency in the target language, and indirectly affect willingness to interact with migrants and attitudes toward migrants' language education. Across two pre-registered experiments ( N  = 531) conducted in Canada, we found that people who were primed with fixed (vs. growth or control) mindsets tended to believe migrants have less potential to improve their English, but were less likely to blame them for their lack of improvement ("not their fault if they can't improve"), suggesting fixed mindsets contribute to mixed attitudes toward migrants. Furthermore, perceived linguistic potential was negatively and blame was positively correlated with contact avoidance and opposition to publicly funded language education for newcomers. These effects held after controlling for political orientations and perceived fluency of the target speaker, suggesting that language mindsets contribute to language judgments that could impact migrants' acculturation experiences.